SISTEM INFORMASI JARINGAN IRIGASI (SIJARI) KABUPATEN SUKOHARJO BERBASIS PROGRAM ARCVIEW GIS 3.3. - Sriyana Sriyana (TEKNIK, 2010)
Data availability of irrigation area authority, discharge data, physical condition of weir, channel condition,hydraulic structure damage, finance needed for recovery etc are sometimes unclear, invalid and lost in data,low service and poor performance, resulting planning interest, monitoring implementation and controlunfulfilled. The purpose of this thesis is to make SIJARI software (Sistem Informasi Jaringan Irigasi )whichcontains data base information of Irrigation in Geographic Information System(SIG), based on Arcviewprogram GIS 3.3. The result of SIJARI software contains all data base information starting from irrigationarea authority, structures damage, channel condition, crop pattern etc, where all data can be fast andaccurately accessible and can be used for pre-plan, planning, implementation, monitoring and control.